2021
DOI: 10.1021/acsaelm.1c00460
|View full text |Cite
|
Sign up to set email alerts
|

Device Optimization of PIN Structured Perovskite Solar Cells: Impact of Design Variants

Abstract: Numerical analysis is a tool that is helping engineers over the past decades in design optimization and low-cost fabrication of solar cell devices. The need of modeling tools is used to deeply analyze a device in a soft environment where the time and cost both can be saved before putting a device into fabrication. In this study, lead iodide-based perovskite solar cells were modeled having several feasible planar pin structures for known electron and hole transport layers. The primarily taken pin device structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 64 publications
1
11
0
Order By: Relevance
“…PSCs typically use a planar architecture in which a perovskite absorber layer is sandwiched between a highly n-doped electron transport layer (ETL) and a highly p-doped hole transport layer (HTL). While some drift-diffusion models comprising only electrons and holes continue to be published [5][6][7], it has repeatedly been shown that migration of ion vacancies is not only present in the perovskite layer but vital to understanding their operation [8][9][10]. These simplistic models, which omit ion migration, are incapable of replicating the dynamic current-voltage or impedance responses of PSCs [2,8,[11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…PSCs typically use a planar architecture in which a perovskite absorber layer is sandwiched between a highly n-doped electron transport layer (ETL) and a highly p-doped hole transport layer (HTL). While some drift-diffusion models comprising only electrons and holes continue to be published [5][6][7], it has repeatedly been shown that migration of ion vacancies is not only present in the perovskite layer but vital to understanding their operation [8][9][10]. These simplistic models, which omit ion migration, are incapable of replicating the dynamic current-voltage or impedance responses of PSCs [2,8,[11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Most important achievements include the development of robust perovskite structures (compositional variations), various routes for effective passivation of crystalline defects, understanding and mitigation of the negative repercussions of ionic motions in perovskite layers, or engineering charge selective contacts with improved chemical and electronic stability. [7][8][9][10][11][12][13] All these points relate to the intrinsic stability of perovskite device structures. To exploit the full potential of perovskite PV technology, longterm operation in harsh weather conditions has to be ascertained.…”
Section: Introductionmentioning
confidence: 99%
“…CGO is also used as photoanode in the dye-sensitized solar cells (DSSCs) . In addition, the use of this substance as a hole transport layer (HTL) in perovskite solar cells has appeared very promising. , Due to the suitable electronic, optical, and chemical properties of CGO, it can also be used in p-channel transparent thin-film transistors (TTFTs), photocatalysts, p–n junctions, UV emitting diodes, H 2 generation, and photodetectors . However, the use of CGO in electronic and electro-optical devices requires the proper electronic connection between this semiconductor and a suitable metal, which always faces challenges.…”
Section: Introductionmentioning
confidence: 99%